2018
DOI: 10.1097/md.0000000000011419
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory confirmation of the effect of occupational sun exposure on serum 25-hydroxyvitamin D concentration

Abstract: Vitamin D concentration is known to correlate with various parameters. A major source of vitamin D is synthesis in the skin; thus, the duration of sun exposure is known to correlate with serum vitamin D levels. We compared serum levels of vitamin D between 2 occupational groups in Korea: the fisherman group, the most sun-exposed, and the general occupation group, relatively less sun-exposed. This study was conducted on 140 healthy fishermen and 140 healthy residents with various occupations, all of whom reside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 24 publications
2
11
0
3
Order By: Relevance
“…However, there was a significant difference in serum total 25(OH)D concentration according to age group. Based on a recent study published by our group, serum total 25 (OH) D levels are the lowest in the 20s but the highest in the 70s [29]. In the present study, the age group of 18 to 65 years had lower serum total 25 (OH) D levels than the age group of over 65 years, consistent with our previous study [29].…”
Section: Discussionsupporting
confidence: 91%
“…However, there was a significant difference in serum total 25(OH)D concentration according to age group. Based on a recent study published by our group, serum total 25 (OH) D levels are the lowest in the 20s but the highest in the 70s [29]. In the present study, the age group of 18 to 65 years had lower serum total 25 (OH) D levels than the age group of over 65 years, consistent with our previous study [29].…”
Section: Discussionsupporting
confidence: 91%
“…The time of year, latitude, skin color, age and use of sunscreen influence skin production 19,4 . The widespread prevalence of hypovitaminosis D can also be attributed to environmental factors, such as air pollution, which reduces sunlight exposure 2,20 .…”
Section: Other Studies That Potentially Support the Role Of Vitamin Dmentioning
confidence: 99%
“…Higher mean vitamin D level (27.04±7.21 ng/ml) found among the fishermen living in coastal areas compared to levels reported in other categories of people by previous Bangladeshi studies signifies the importance of sun exposure to maintain adequate concentration of serum vitamin D. In a similar study, Lee et al found that healthy fishermen who lived in a coastal city in South Korea had 1.7 times higher mean serum concentration of 25(OH)D compared to the general occupation group (23.74±8.88ng/mL and 13.60 ± 6.43, p<.001) [13]. Despite having an abundant exposure to the sun, 71% of our study population had low vitamin D in terms of levels mentioned in the guideline of Endocrine Society.…”
Section: Discussionmentioning
confidence: 74%
“…Despite having an abundant exposure to the sun, 71% of our study population had low vitamin D in terms of levels mentioned in the guideline of Endocrine Society. Similarly, the South Korean study reported low vitamin D levels in 78% of healthy coastal fishermen despite adequate sun exposure [13]. In India, 84.9% of the healthy adult population of the coastal regions of Odisha had low vitamin D levels [14].…”
Section: Discussionmentioning
confidence: 99%